2014
DOI: 10.1152/ajpcell.00274.2014
|View full text |Cite
|
Sign up to set email alerts
|

Acquired cisplatin resistance in human ovarian A2780 cancer cells correlates with shift in taurine homeostasis and ability to volume regulate

Abstract: Sørensen BH, Thorsteinsdottir UA, Lambert IH. Acquired cisplatin resistance in human ovarian A2780 cancer cells correlates with shift in taurine homeostasis and ability to volume regulate. Am J Physiol Cell Physiol 307: C1071-C1080, 2014. First published September 24, 2014; doi:10.1152/ajpcell.00274.2014.-Cisplatin resistance is a major challenge in the treatment of cancer and develops through reduced drug accumulation and an increased ability to avoid drug-induced cell damage, cell shrinkage, and hence initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 69 publications
9
77
1
Order By: Relevance
“…The anti-tumor mechanism of Tau is mainly related to Tau-induced apoptosis, synergism, and attenuation [913], via regulating the expression of key genes at both the transcriptional and translational levels. For example, Zhang et al showed that Tau prompted the transcription and translation of the PUMA gene in HT-29 colorectal cancer cells [10], and Sorensen et al indicated that Tau increases LRRC8A expression in wild-type A2780 cells [22]; however, the specific mechanisms underlying these effects have not been elucidated. In the present study, we investigated the impact of Tau on apoptosis in CRC cells by changing the expression of MST1 gene or inhibiting the JNK pathway, aiming to investigate the roles of the MST1-JNK signaling pathway in the Tau-induced apoptosis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor mechanism of Tau is mainly related to Tau-induced apoptosis, synergism, and attenuation [913], via regulating the expression of key genes at both the transcriptional and translational levels. For example, Zhang et al showed that Tau prompted the transcription and translation of the PUMA gene in HT-29 colorectal cancer cells [10], and Sorensen et al indicated that Tau increases LRRC8A expression in wild-type A2780 cells [22]; however, the specific mechanisms underlying these effects have not been elucidated. In the present study, we investigated the impact of Tau on apoptosis in CRC cells by changing the expression of MST1 gene or inhibiting the JNK pathway, aiming to investigate the roles of the MST1-JNK signaling pathway in the Tau-induced apoptosis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…10C) and an inability to volume regulate. 95 Furthermore, 18 hour cisplatin treatment results in a 2-2.25 fold increase in the LRRC8A protein content in the cisplatin-sensitive A2780 cells (Fig. 12C), whereas the protein expression in resistant cells was unaffected by (Fig.…”
Section: The Lrrc8 Family -Important Components Of Vrac and Vsoacmentioning
confidence: 90%
“…Comparing (i) non-adherent cisplatin sensitive EATC with adherent, cisplatin resistant ELA, 93 (ii) A2780 WT with A2780 RES (Fig. 10F) 94,95 as well as (iii) colorectal cancer cell lines (LoVo, SW480, DLD1, HT-29, HCT116) with normal colonocytes 96 it appears that TauT expression is high in drug resistant cells compared to their drug-sensitive parental counterparts which support earlier findings in kidney cells that cisplatin resistance complies with high expression of functional TauT. 97 Furthermore, similar to findings in colorectal cancer by Yasunaga and Matsumuru 96 we see that TauT knockdown enhances drug sensitivity in cisplatinresistant ELA cells (Fig.…”
Section: Vsoac -Cell Death and Drug Resistancementioning
confidence: 99%
“…cisplatin). [9][10][11][12][13] Additionally, patients with a low LRRC8D gene expression in their ovarian cancers displayed reduced survival. 10 Similarly, LRRC8D expression was shown to be essential for the cytotoxic effect of the antibiotic blasticidin S.…”
Section: Introductionmentioning
confidence: 99%